Persuasion in Political Posters: A Case Study of Posters during Haqeeqi Azadi March of PTI - Dildar Ahmed; Dr. Musarat Yasmin Alvi; Dr. Raza Waqas Ahmad (Indus Journal of Social Sciences, 2025)
The present study explores randomly selected political posters of Pakistan Tahreek-e-Insaf used in a political campaign “Haqeeqi Azadi March” to find out the patterns of persuasion. The researcher has randomly chosen three digital posters from the Twitter handle @ptiofficial. The selected material has been analyzed qualitatively by applying Kress & Van Leeuwen (2020) multimodal approach for social semiotic analysis, Kress & Van Leeuwen (2006) visual grammar, and Van Leeuwen (2008) critical discourse analysis of social actors. The study results will show the systematic use of different techniques to convince the audience to win their support for the mentioned political party. The study will be beneficial for those interested in studying semiotics and multimodal means of communication in the present era of digital socialization.